The Influence Of Organizational Culture And Work Discipline On Customer Service At Pt. Sapek Child's Cord - Permata Lestary; Mulyono; Muhammad Ridwan (Smart International Management Journal, 2024)
This study aims to examine and analyze the influence of organizational culture and work discipline on customer service at PT. Korda Anak Sapek. This research is a quantitative study. The sampling technique used is saturation sampling, meaning all members of the population are used as samples. The number of samples used is 80 respondents. The data obtained were analyzed using validity tests, reliability tests, classical assumption tests, multiple linear regression tests, hypothesis tests, and determination coefficient tests using the SPSS program (Statistic Package for the Social Sciences). The results of the partial testing for organizational culture have a significant effect on customer service. Work discipline has a significant effect on customer service. Meanwhile, simultaneous testing for organizational culture and work discipline has a positive and significant effect on customer service at PT. Korda Anak Sapek.